2021
DOI: 10.1111/lnc3.12430
|View full text |Cite
|
Sign up to set email alerts
|

Sentence comprehension in ageing and Alzheimer's disease

Abstract: The ability to correctly interpret complex syntax and long sentences is gradually impaired as people age. Typical ageing is characterised by working memory deficits, which are thought to play an important role in determining whether syntax can be comprehended correctly, and neurodegenerative conditions such as Alzheimer's disease (AD) are thought to exacerbate these limitations. Furthermore, declines in processing speed appear to cause increasing difficulty in the proper allocation of cognitive resources neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 81 publications
1
3
0
1
Order By: Relevance
“…Sung et al [64] found a significant effect of word order; canonical sentences were better comprehended than sentences with syntactic movement. Similar findings were also found in other studies (e.g., [65‒67]). In the current study, the older adult participants were tested using a syntactic production task.…”
Section: Introductionsupporting
confidence: 92%
“…Sung et al [64] found a significant effect of word order; canonical sentences were better comprehended than sentences with syntactic movement. Similar findings were also found in other studies (e.g., [65‒67]). In the current study, the older adult participants were tested using a syntactic production task.…”
Section: Introductionsupporting
confidence: 92%
“…Our approach, being in line with most neurocognitive instrument scoring guidelines which score examinees’ answers as either correct or false, may bypass potential bias stemming from the complex interplay between personality traits, non-cognitive symptoms of neurocognitive disorders (e.g., impulsivity) and cognitive and functional performance (Rouch et al 2019 ; Sakurai et al 2020 ; Cerni et al 2021 ; Giannakis et al 2021 ). Furthermore, it may be reckoned that differences in the length of questions of the two here studied auditory stimuli-based dysnomia instruments may have biased our observations since individuals with cognitive impairment face difficulties in understanding long sentences (van Boxtel and Lawyer 2021 ). In such a case, low performance on WoFi and WoFi-brief may be attributed not only to dysnomia but also to comprehension difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à compreensão de frases existem diversos estudos (Kempler & Goral, 2008;Murdoch et al, 1987) que foram elaborados com base no discurso espontâneo, verificando-se que não existiam alterações ao nível sintático, uma vez que as pessoas com DA não faziam omissões dos morfemas gramaticais, mantinham a estrutura sintática e o emprego da classe de palavras. Atualmente (Boxtel & Lawyer, 2021), com o uso de testes mais específicos, pode concluir-se que as pessoas com DA apresentam dificuldades na compreensão de frases complexas, com voz passiva e frases extensas. Estas dificuldades poderão estar relacionadas com o efeito da sobrecarga na capacidade de armazenamento da memória a curto prazo e outros fatores que envolvem variáveis relacionadas com aspetos semânticos e com efeitos de processamento.…”
Section: Cognição E Linguagem Na Daunclassified